Depiction of History in Train to Pakistan: Fiction as Social History of Khushwant Singh's Novels: Exploring the Social Issues in Khushwant Singh's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Khushwant Singh has an extensive comprehension of our social issues. His compositions portray with compel, brightness and energy the issues which torment and torment the Indian soul in contemporary times. He has called attention to the downsides that torment India, which hold her over from advancing full steam on the way of advance. In the event that we try to comprehend the India of today which we adore so energetically, we locate a clear impression of it in his compositions. His group of work underlines the particular components of numerous social issues which draw in our consideration and it tries to give us an ability to read a compass, whither we are to progress and how.